Linkage between a major gene for powdery mildew resistance and an RFLP marker on chromosome 1R of rye - Wricke G; Dill P; Senft P (Plant Breeding, 1996)
DNA samples from an F2 progeny which segregated for resistance to powdery mildew were bulked for resistant and susceptible individuals. In a segregant analysis, genomic rye probes which had been localized previously in a linkage map of rye were systamatically screened for polymorphisms between these bulks. An RFLP marker located on linkage group 1RS was found to be tightly linked to a dominant mildew resistance gene. This is first publication mapping a major gene for mildew resistance in rye.
Keywords: Erysiphe graminis; Molecular marker; Powdery mildew; Resistance; RFLP; Secale cereale